2010
DOI: 10.2224/sbp.2010.38.4.433
|View full text |Cite
|
Sign up to set email alerts
|

Shared mental models as moderators of team process-performance relationships

Abstract: The effects of shared mental models on the relationship between episodic team behavioral processes and performance were investigated, while teams were using an experimentally stimulated construction project planning program. The results indicated that episodic team processes made positive contributions to the team performance. Furthermore, a hierarchical linear regression indicated that the convergence of shared teamwork mental models moderated the effects of team processes on team performance. Specifically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 0 publications
2
17
0
1
Order By: Relevance
“…In return, team processes loaded significantly on team effectiveness (Mathieu et al, 2000). Similar results pertaining to shared teamwork cognition were found by Team Chemistry 4 Zhou and Wang (2010) who aimed at capturing the moderating effect of SMM on the relationship between team process and performance. To meet this end, 50 three-person teams in a simulated construction project planning program were examined.…”
supporting
confidence: 60%
“…In return, team processes loaded significantly on team effectiveness (Mathieu et al, 2000). Similar results pertaining to shared teamwork cognition were found by Team Chemistry 4 Zhou and Wang (2010) who aimed at capturing the moderating effect of SMM on the relationship between team process and performance. To meet this end, 50 three-person teams in a simulated construction project planning program were examined.…”
supporting
confidence: 60%
“…For example, Bradley et al (2012) found that psychological safety, an emergent state characterized as a shared belief that a team's climate is one where it is safe to speak up and take risks, moderates the relationship between task conflict and team performance. Similarly, Zhou and Wang (2010) found that the relationship between team processes and performance was moderated by shared mental models, an emergent state defined as the knowledge shared by team members. In this work, we posit that the relationship between innovation processes and performance will be moderated by team goal clarity and commitment, whereas the relationship between innovation processes and reputation will be moderated by team affective tone.…”
Section: Emergent States As Moderatorsmentioning
confidence: 96%
“…and in turn, to coordinate their actions and adapt their behavior to demands of the task and other team members" (Cannon-Bowers, Salas, & Converse, 1993, p. 228). The cognitive concept of SMM has been used to study team operations in the military, education, industry, and high-technology developers (see Johnson & Lee, 2008;Levesque, Wilson, & Wholey, 2001;Mathieu, Heffner, Goodwin, Salas, & Cannon-Bowers, 2000;Zhou & Wang, 2010). However, sport studies utilizing SMM remain scarce.…”
mentioning
confidence: 99%